A collaborative culturally-centered and community-driven faith-based opioid recovery initiative: the Imani Breakthrough project. Issue 6 (2nd November 2021) - Bellamy, Chyrell D.; Costa, Mark; Wyatt, Janan; Mathis, Myra; Sloan, Ariel; Budge, Mariana; Blackman, Kimberly; Ocasio, Luz; Reis, Graziela; Guy, Kimberly; Anderson, Reverend Robyn; Stewart Copes, Michelle; et al.
ABSTRACT: The opioid crisis has become a complex and multifaceted societal challenge. For Black and Latinx individuals, access and engagement in effective treatment remains a high concern. Developed as the result of a collaborative culturally-responsive initiative, the Imani Breakthrough program has been hosted by Black and Latinx churches. It has helped participants improve their lives, feel valued by society, connect with others, and have positive relationships with their loved ones and community. This brief report highlights preliminary findings which demonstrate the strength of this model of care involving community churches, highlighting the need/potential for continued collaboration efforts.